Aspectos neuropsicológicos do transtorno obsessivo-compulsivo - Leonardo Fontenelle (Brazilian Journal of Psychiatry, 2001)
Neuropsychology is contributing to elucidate the nature of brain dysfunction associated with obsessive-compulsive disorder (OCD). Neuropsychological studies of individuals with subclinical and clinical obsessive-compulsive symptoms are reviewed here. It was observed that OCD patients may display impaired "reality monitoring", memory for actions, non-verbal memory, visuo-spatial abilities, and executive functions. Some specific neuropsychological findings are associated with different clinical characteristics such as gender, duration of disease, severity of symptoms, and response to drug treatment. Comparative studies suggest that the neuropsychological dysfunction associated with OCD is significantly different from that seen in major depressive disorder or schizophrenia. However, many similarities were observed between patients with OCD and patients with social phobia, body dysmorphic disorder, and trichotillomania. Furthermore, studies suggest that certain neurochemical abnormalities may underlie particular neuropsychological dysfunctions found in OCD. Despite many heterogeneous results, the reviewed data seems to support the pathophysiological theory centered in the dysfunction of the fronto-striatal circuits in OCD.